PEMUNGUTAN SUARA ULANG DALAM PEMILIHAN BUPATI KABUPATEN INDRAGIRI HULU PROVINSI RIAU (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PHP.BUP-XIX/2021): Re-voting in the regent election of Indragiri Hulu Regency, Riau Province (Study of Constitutional Court Decision Number 93/PHP.BUP-XIX/2021) - Regina Zetia; Wiratno (Reformasi Hukum Trisakti, 2024)
The Local Election in Indragiri Hulu Regency witnessed multiple infringements. Consequently, in line with Constitutional Court Decision No. 93/PHP.BUP-XIX/2021, a new election for regent and deputy regent is mandated. This study focuses on the grounds for requesting a recount in the election dispute for the Regent of Indragiri Hulu Regency and explores the legal implications of a re-vote as per Constitutional Decision No. 93/PHP.BUP-XIX/2021. Employing a normative legal research approach. Secondary data, gathered through a literature review, is qualitatively processed, and conclusions are drawn through deductive logic. Research findings reveal violations such as breaching PKPU provisions, manipulating the vote count recapitulation, failure to submit Model C notifications to the Election Supervisory Body, tampering with certain ballots, and the lack of neutrality by village heads violate Article 2 of Law No. 7 of 2017 concerning General Elections and Article 22E of the 1945 Constitution. This provides a substantial basis for implementing a recount in accordance with Constitutional Decision No. 93/PHP.BUP-XIX/2021.